2019
DOI: 10.1071/es19004
|View full text |Cite
|
Sign up to set email alerts
|

The synoptic-dynamics of summertime heatwaves in the Sydney area (Australia)

Abstract: Motivated by the record-breaking heatwaves of early 2017, the synoptic structure and evolution of summer (December–February) heatwaves in the Sydney area is investigated through composite and trajectory analyses. In the upper troposphere, the main features of the composite structure are an isolated upper-tropospheric anticyclonic potential vorticity (PV) anomaly to the south-east of Australia and cyclonic anomalies to the east and south. Back trajectories starting from within the upper-tropospheric anticycloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…TAS, experience longer hot spells during periods when RRWPs occur. Interestingly, Northern Australia does not show such an association, which agrees with previous studies showing different dynamical pathways for Northern and Southern Australian heatwaves(Parker et al, 2019;Quinting et al, 2017). Other statistically significant areas over land include parts of South February 2004 heatwave (7-22 February) lasted for 16 days.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…TAS, experience longer hot spells during periods when RRWPs occur. Interestingly, Northern Australia does not show such an association, which agrees with previous studies showing different dynamical pathways for Northern and Southern Australian heatwaves(Parker et al, 2019;Quinting et al, 2017). Other statistically significant areas over land include parts of South February 2004 heatwave (7-22 February) lasted for 16 days.…”
supporting
confidence: 88%
“…Broadly, heatwaves in SEA (Fig. 1), comprising the states of Victoria (VIC), New South Wales (NSW), South Australia (SA), and Tasmania (TAS), are associated with slow-moving transient anticyclonic upper-level potential vorticity (PV) anomalies over the Tasman Sea (e.g., Marshall et al, 2013;Parker et al, 2014a;Quinting et al, 2017;Parker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research focused on identifying the role of atmospheric blocking for heatwave initiation and persistence has involved both composite analysis (e.g., Gibson et al, 2017; Loughran et al, 2018; Parker et al, 2019; Parker, Berry, Reeder, & Nicholls, 2014; Pfahl & Wernli, 2012; Risbey et al, 2017; Tozer et al, 2020) and Lagrangian trajectory analysis (e.g., Pfahl et al, 2015; Quinting et al, 2018; Quinting & Reeder, 2017; Schumacher et al, 2019). Composite analysis involves extracting relevant atmospheric fields (e.g., pressure and potential vorticity) for days classified as part of a heatwave event and aggregating them to identify key synoptic features associated with these events.…”
Section: Introductionmentioning
confidence: 99%
“…No equivalent local sensible heating of the air occurs during the THWs in Ningaloo and Hobart (Figures 8E,F). Previous studies using lagrangian tracking of air parcels have also suggested that adiabatic warming of descending air in the hours and days prior to a THW may play an important role in these events (Quinting and Reeder, 2017;Quinting et al, 2018;Parker et al, 2019). Although the composite analysis of vertical velocity hints at the possibility of these THWs being influenced by the vertical motion of air, other techniques would be needed to determine the relative importance adiabatic warming.…”
Section: Discussionmentioning
confidence: 99%